Determinants of Performance of 12-Year-Old Soccer School Players in Central Java - Cahyo Yuwono; Adi S; Mohamad Annas; Agus Darmawan; Bhayu Billiandri; Dwi Tiga Putri; Ade Bagus Pratama (Universitas Negeri Semarang, 2024)
This study aims to predict the determinants of performance in the 12-year age group. This study uses a mixed methods approach with a diverse research method (concurrent), namely a balanced quantitative and qualitative hybrid model (concurrent triangulation). The sample of this study amounted to 201 KU 12 soccer school athletes in Central Java. Anthropometry is measured using anthropometric measurements, including head circumference, arm length, leg length, arm circumference, abdominal circumference, thigh circumference, and chest circumference. 2) Body Mass Index (BMI) uses measurements of height and weight. Biomotor ability tests include 1) Speed Running speed using a 20m running test on a straight line with the fastest possible time measured in seconds. It was measured as quickly as possible using units of seconds. 2) Flexibility Flexibility using the sit and reach test is measured in centimeters (cm) 3) Strength Measuring leg muscle strength using the leg strength test using a leg dynamometer. 4) Aerobic endurance VO2 Max ability is measured using a 12-minute running test according to the Wilcoxon Signed Rank Test Protocol 5) Coordination Eye-foot coordination test with Soccer Wall Voley Test. Factors that affect the performance of 12-year-old soccer students are height, Body Mass Index. 20 meter run, strength, coordination and biomotor. While anthropometric and psychological factors as a whole there is no relationship. In the future, further research is needed with playing position-based analysis.